2015
DOI: 10.1073/pnas.1500012112
|View full text |Cite
|
Sign up to set email alerts
|

Why chloroplasts and mitochondria retain their own genomes and genetic systems: Colocation for redox regulation of gene expression

Abstract: Chloroplasts and mitochondria are subcellular bioenergetic organelles with their own genomes and genetic systems. DNA replication and transmission to daughter organelles produces cytoplasmic inheritance of characters associated with primary events in photosynthesis and respiration. The prokaryotic ancestors of chloroplasts and mitochondria were endosymbionts whose genes became copied to the genomes of their cellular hosts. These copies gave rise to nuclear chromosomal genes that encode cytosolic proteins and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
211
1
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 255 publications
(218 citation statements)
references
References 101 publications
(136 reference statements)
4
211
1
2
Order By: Relevance
“…Specifically, a mixture of nuclear-and mt-encoded products physically interact to form the multisubunit oxidative phosphorylation (OXPHOS) enzyme complexes (Allen 2015) and components of the mt translational machinery (particularly ribosomes; Maier et al 2013). The nuclear and mt genomes are replicated and inherited in fundamentally different ways, resulting in fascinating coevolutionary dynamics that have important consequences for health, aging, and eukaryotic diversification (Dowling 2014;Hill 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, a mixture of nuclear-and mt-encoded products physically interact to form the multisubunit oxidative phosphorylation (OXPHOS) enzyme complexes (Allen 2015) and components of the mt translational machinery (particularly ribosomes; Maier et al 2013). The nuclear and mt genomes are replicated and inherited in fundamentally different ways, resulting in fascinating coevolutionary dynamics that have important consequences for health, aging, and eukaryotic diversification (Dowling 2014;Hill 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Yeast cells also possess a mechanism for mitophagy, but so far this machinery was reported to be used mainly for non-selective, bulk removal of mitochondria in the stationary phase or under nitrogen starvation (for a review, see Müller et al, 2015) and was not shown to be activated by uncouplers (Mendl et al, 2011). At the same time, it was suggested that mitochondrial inner membrane region can be enriched with the proteins encoded by the mtDNA adjacent to this region (the CoRR hypothesis, see Allen, 2015 for a review). Therefore, coupling of mitochondria quality control and negative selection of mutated mtDNAs is theoretically possible.…”
Section: Introductionmentioning
confidence: 99%
“…Current debate on symbiogenesis has focused on the role of mitochondria at the origin of eukaryotes. Proponents of symbiogenesis, or endosymbiotic theory, have it that symbiosis is a rare but crucial mechanism of evolution (7,8,9,10,11,12,13,14). Proponents of the opposing gradualist view admit that endosymbiosis occurred when mitochondria arose, but hold that it had no impact on the evolutionary process (15,16,17).…”
Section: William F Martinmentioning
confidence: 99%
“…ii) One more symbiogenic association gave rise to the first cell with plastids (7,9,10,11), from which all plants (now called archaeplastida) descend. iii) Secondary symbioses occurred among eukaryotes to give rise to algae with secondary plastids (83).…”
Section: Gradualist Versions Of Symbiogenesismentioning
confidence: 99%